Towards a Sustainable Smart City: The Role of Big Data and Internet of Things (IoT) in Urban Governance - Rustiyana Rustiyana (Pt. Anagata Sembagi Education, 2025)
The rapid growth of urban populations demands smarter, more efficient, and sustainable city governance. This study aims to analyze the role of Big Data and the Internet of Things (IoT) in supporting urban governance toward a sustainable smart city, with a focus on their contributions to environmental, economic, and social sustainability. The research employed an exploratory-descriptive qualitative method through in-depth interviews, community surveys, field observations, as well as secondary data analysis from official reports and academic publications. Qualitative data were analyzed using thematic analysis, while quantitative data were processed with descriptive and inferential statistics. The findings reveal that the integration of Big Data and IoT enhances the effectiveness of city government decision-making through real-time data and predictive analytics. The application of these technologies contributes to emission reduction, energy efficiency, transportation optimization, increased citizen participation, and operational cost savings. However, implementation still faces obstacles such as limited network infrastructure, digital literacy gaps, high maintenance costs of devices, as well as data security and privacy issues. This study recommends strengthening regulations, fostering government–private sector collaboration, and implementing public education programs to expand technology adoption. These findings highlight that the success of a sustainable smart city requires synergy between technological innovation, inclusive policies, and active community engagement.